O mito da inclusão produtiva: o discurso ideológico de cidadania, inclusão social e crescimento econômico do estado brasileiro de FHC à Dilma - ELOI, Núbia Machado (Universidade Federal do Pará, 2015)
This master’s degree dissertation presents as the main goal to analyse which is the productive inclusion conception. It’s distinguished because of strength work qualification action. These actions increased and became more frequently during Lula’s Government, in 2003, and were handed by Combat Against Hungriness, Social and Development Ministery, as a contracditory assay of economics development and combat against the poorness in Brazil. Concern to our specific aims, we try to analyse in which moment the productive inclusion begins being spread by Brazilian Federal Government; we also investigated official documents of Brazilian Government as well as those of International Institutions that are related to the term productive inclusion. We also analysed official documents in order to understand which concepts of productive inclusion the ministry takes. Our methodological treatment with our study object was done through qualitative approach, guided by documental and bibliographic research. So, we tried to understand productive inclusion conception by analyzing 13 (thirteen) documents as well as electronic information at the web sites of institutions like MTE, CEPAL and MDS. The results of our research allow us to conclude that productive inclusion handed by PT (Workers Party) government (Lula Silva and Dilma Rousseff) is supported by an ideological speech of citizenship, social inclusion, economics growing, leadership, development of attributes that take part on the role of professional education and qualification that insert poor people in the job market. So, we conclude that these conceptions and terms are able to hide structural unemployment, work’s exploration, social differences. At the same time these conceptions raise, through the insert of this population in the capital’s world, the acceptance their general position into this society: the superpopulation that capitalism accumulation needs.